Stress hyperglycaemia or diabetes mellitus in cervicofacial infections? A Maxillofacial Surgery Trainee Research Collaborative (MTReC) study. Issue 8 (October 2022) - ,; Kent, Samuel; Dawoud, Basim; Henry, Alastair; McDonald, Chris; Hennedige, Anusha; Kulkarni, Raghav; Logan, Greg; Exley, Rebecca; Kyzas, Panos; Morrison, Roderick; McCaul, James; et al.
Abstract: Diabetes mellitus (DM) is thought to be associated with poor outcomes in cervicofacial infections (CFI), yet little is known about the prevalence of DM in these cases. Stress hyperglycaemia (SHG), a normal physiological response to inflammation, is distinct from DM, though they overlap and may be conflated. We aimed to establish the prevalence of DM and SHG in CFI, and to determine the effect of each on severity of disease and outcome measures. The Maxillofacial Surgery Trainee Research Collaborative (MTReC) carried out an audit of all patients with CFI admitted to 25 hospitals between May and October 2017. To the best of our knowledge this created the largest prospective database on CFI, with information collected on presentation, source of infection, biological data, and outcomes. We recorded 1002 admissions, of which 78 (7.8%) had DM. Random blood glucose was measured on admission in 401 patients (40%), of which 45 (11%) displayed SHG. Patients diagnosed with DM were more likely to have infections arising from a salivary source (13% vs 4%, p < 0.00), more returns to theatre (9% vs 2%, p < 0.00), and a longer hospital stay (median (range) 2 (0-34) vs 1 (0-139) day, p = 0.01) than non-DM patients. In contrast, patients with SHG had more severe disease (multiple fascial spaces involved in 59% vs 19%, p = 0.01, and systemic inflammatory response syndrome present in 66% vs 45% p = 0.03), but did not have significantly more returns to theatre (2% vs 3%, p = 0.91) or longer stays in hospital (median (range) 1 (0-63) vs 1 (0-6), p = 0.55) than normoglycaemic patients. The prevalence of DM in our cohort was only marginally higher than in the general population, despite previous retrospective case reviews suggesting a significantly higher prevalence. SHG was not associated with poor outcomes in our cohort, but is likely to be associated with a small increased risk of subsequent diagnosis of DM, which can be quantified using a calculator tool. On discharge, it is important to give appropriate advice about diet, lifestyle, exercise, and weight loss to all patients with CFI.